The Effect of formative assessment on students’ grades in learning English - Ismail, Ismail; Tini, Tini (Maspul Journal of English Studies, 2020)
Objective: Assessment is an important for learning and teaching and is an important component for further development if they use the right approach. This study focuses primarily on how formative assessment, as a type of favorable assessment, can be an effective contributor to increasing student motivation in learning English. Method: This study explores the results of formative assessments through questionnaires for 24 students and 5 for teachers, in the SMA 1 Alla-Enrekang, where English is taught as a foreign language. Result: It is assumed that formative assessment has a major influence on what students learn and how the teacher validates. Discussion: Formative assessment can help teachers anticipate initial concerns for student disparity in the development of learning. Therefore, this assessment method cannot accurately assess the frequency of student acquisition, because it varies from one teacher to another and subjects with other subjects.